Tafsir Maqasidi Muhammad Talbi dan Abdul Mustaqim sebagai Pendekatan Alternatif dalam Menafsirkan Al-Qur’an - Iqbal Kholidi (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2024)
Because the Qur'an is authentic in every era, the Qur'an should be interpreted appropriately according to the demands of life. Basically, life has changed in various situations and conditions, including lifestyle, human relations, globalization, migration, advances in technology and knowledge. Modernization has raised serious problems regarding the Koran as the main source of Islamic jurisprudence which appears "unworkable", except by a handful of Muslims. If there is no reinterpretation of the verses of the Qur'an, it is very likely that Islamic jurisprudence will be rejected, considered irrelevant and counter-productive to the needs of life. To be able to carry out re-interpretation, a Maqashidi interpretive approach is needed in interpreting the Al-Qur'an, especially in ethical-legal verses. There are two significant implications in the maqashidi interpretation approach; First, the maqashid interpretation paradigm is a mindset and way of looking at the Al-Qur'an and its interpretation with the concept of maqashid al-shari'ah as the starting point. The concept of maqashid is the main basis for reasoning and forms an interpretation system. Second, the interpretive method of the maqashidi approach emphasizes three pillars, namely historical awareness (al-wa'yu al-tarikh), theoretical awareness (al-wa'yu al-nazhari), practical awareness (al-wa'yu al-nazhari) . Practically, the steps in maqashidi interpretation are contextualization, decontextualization and recontextualization.